Scaling-Up Orange-fleshed Sweetpotato Through Agriculture and Nutrition (SUSTAIN) in Malawi - International Potato Center (2017)
During the 2016/2017 season, 32,040 households received planting material. Out of these, 19,000 were reached with nutrition messaging. Nankhwali Farm in Mulanje continued to multiply and supply planting material from an 11 hectare farm but Ripple Africa is Nkhata Bay has shown interest to do the multiplying in the Northern region from this year. Universal Industries continued to produce BETA crisps, purée and bread from orange-fleshed sweetpotato (OFSP). The project found that using one large-scale vine multiplier was an effective strategy.